2011
DOI: 10.1177/1358863x11408639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of darbepoetin alfa on endothelial progenitor cells and vascular reactivity in chronic kidney disease

Abstract: Endothelial progenitor cells (EPCs) are thought to be important for maintaining normal vascular function. We conducted a prospective study evaluating the effect of the erythropoiesis-stimulating agent darbepoetin alfa on EPCs and vascular function in patients with chronic kidney disease (CKD), with or without diabetes. Thirty subjects with CKD (20 subjects with type II diabetes mellitus and 10 without diabetes mellitus) received weekly subcutaneous administration of darbepoetin alfa for 4 weeks. EPCs were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…It is now becoming increasingly clear that EPO plays a protective role in the body outside of its erythropoietic effects. Previous studies identified the protective effects of EPO on different molecular pathways in ischemic tissues in the heart, kidney, and brain [5,14,15]. There are very few studies describing an effect of EPO treatment on diabetic cardiac tissue [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is now becoming increasingly clear that EPO plays a protective role in the body outside of its erythropoietic effects. Previous studies identified the protective effects of EPO on different molecular pathways in ischemic tissues in the heart, kidney, and brain [5,14,15]. There are very few studies describing an effect of EPO treatment on diabetic cardiac tissue [16].…”
Section: Discussionmentioning
confidence: 99%
“…There are several drugs that demonstrated improvement in endothelial function including HMG-CoA reductase inhibitors, [24][25][26] erythropoietin (and analogues), 27 and modulators of the renin-angiotensin system. [28][29][30] The data derived from this study indicate that oral administration of sodium nitrite in the doses administered is safe and the 80 mg BID dose may afford protection against worsening endothelial function among patients with PAD and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Erythropoietin (EPO) receptors are widely distributed in both hematopoietic cells and non-hematopoietic cells, including neurons, cardiomyocytes, peritubular and mesangial cells, and vascular cells such as endothelial and smooth muscle cells (Khoshdel et al, 2008). Although several reports have demonstrated that ESAs have potential benefits against endothelial dysfunction (Bahlmann et al, 2004;Mohler et al, 2011;Toba et al, 2011), these endothelial protective effects of ESAs have been observed under doses that had no influence on hemoglobin, and it is unclear whether appropriate treatment of ESA exerts endothelial protective effects under amelioration of anemia.…”
Section: Introductionmentioning
confidence: 98%